Force Majeure : An International Comparative Analysis - Copeman, Julian,; Garb, Louis,; Mendoza, Richard, (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2025)
This comprehensive work provides a detailed analysis of force majeure across fifty diverse jurisdictions, representing both civil and common law traditions, demonstrating their similarities and differences. Through a carefully structured questionnaire answered by legal experts in each country, the editors have created a resource that allows practitioners to quickly grasp how this critical doctrine is defined, interpreted, and applied worldwide. The purpose of the book is to offer not merely academic analysis but practical guidance to lawyers advising clients on cross-border transactions and disputes thereby saving them time and expense.